Dangerous Liaisons: A 'Big Four' Framework that Provides a 'Hint' to Understanding an Adversary's Strategy for Influence. Issue 3 (16th April 2019) - Verrall, Neil; Dunkley, Mark; Gane, Toby; Byrne, Richard
Abstract : Beliefs, attitudes and behaviour can be influenced in myriad ways. History has consistently demonstrated the struggle between protagonist and antagonist to win over 'the people', often through the simultaneous promotion and destruction of places, icons, myths, symbols and stories. Neil Verrall, Mark Dunkley and Toby Gane, three army reserve officers, and Richard Byrne, an independent geographer, describe four interconnected ways in which hostile state actors or non-state terrorist groups might attempt to influence their target audiences as part of strategy.